KOMPETENSI GURU SEKOLAH DASAR DAN PERMASALAHANNYA DALAM IMPLEMENTASI KURIKULUM MERDEKA: TELAAH KRITIS TERHADAP PEMAHAMAN, PRAKTIK, DAN DUKUNGAN SISTEMIK - Ananda, Rizki; Nurfazira; Oktavia, Dwi Tasya; Febriani, Fanisa; Wulandari, Widia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of the Independent Curriculum at the Elementary School (SD) level presents significant challenges related to teacher competency and readiness. This study aims to critically analyze the understanding, practice, and systemic support for teacher competency in this context. The method used is a literature study with a qualitative approach, reviewing various sources of journals and related scientific articles. The results of the study indicate that teacher competency, including pedagogical, professional, social, and personality, affects the effectiveness of curriculum implementation. The main challenges identified include a lack of in-depth understanding of the philosophy of the Independent Curriculum, limitations in designing differentiated learning, and minimal support for adequate facilities and training. Systemic support from the government and educational institutions is also considered important for the success of the implementation.